WT1 Inhibits Human Renal Carcinoma Cell Proliferation and Induces G2/M Arrest by Upregulating IL-24 Expression. (23rd July 2022) - Jing, Y. J.; Lin, L. C.; Chen, L. L.; Huang, Z. E.; Qin, H. C.; Li, S. B.; Chen, Z. H.
Abstract : The transcription factor Wilms' tumor 1 (WT1) is involved in development, tissue homeostasis, and disease. However, the exact roles and the mechanisms of WT1 in renal carcinoma are not well understood. Therefore, in this study, we evaluated the ability of WT1 to block proliferation in renal carcinoma cells in vitro. Experimental analysis showed that WT1 overexpression inhibited the proliferation of renal carcinoma A498 cells and promoted arrest at the G2/M checkpoint. RNA-Seq identified differentially expressed genes, including IL-24, related to both the cell proliferation and the cell cycle. WT1 overexpression upregulated IL-24 expression, and IL-24 overexpression induced G2/M arrest. ChIP-Seq identified JUN as a direct target of WT1 in A498 cells, in which positive regulation was shown by RT-qPCR. It has been shown that the transcription factor JUN can regulate IL-24 expression, and therefore, we hypothesize that WT1 might regulate the IL-24 through JUN. Furthermore, analysis based on TCGA datasets showed that the expression of WT1-regulated genes, including TXNIP and GADD45A, was significantly correlated with the stage and histological grade of tumors, with high levels linked to favorable prognoses. Our results demonstrated that the overexpression of WT1 upregulates IL-24, leading to G2/M checkpoint arrest to reduce proliferation. These results indicate that regulation of IL-24 by WT1 inhibits proliferation and may represent a potential target for treating renal carcinoma.